The Role of Teachers and Parents in Overcoming The Difficulties of Learning Mathematics for Slow Learner Students During the Covid-19 Pandemic - Erika Erika; Juli Asmida Rambe; Ana Mujriyanti; Siti Mayang Sari; Akmaluddin Akmaluddin (Journal on Education, 2023)
Student learning outcomes cannot be said to be optimally successful for slow learning children. Online learning is not a good solution. This is supported by not all parents and teachers play an optimal role. This problem is one of the reasons for conducting research which aims to examine the role of teachers and parents in overcoming learning difficulties for slow learners during the Covid-19 pandemic. The type of research used by researchers is qualitative, with a descriptive research design. There were 3 subjects used by the researcher, namely one subject teacher. Mathematics, one parent of a student with special needs, and one school principal. Use online interviews and observation methods to collect data. The data analysis technique used is data simplification, data presentation and conclusion. The results of this study indicate that the teacher's role is the existence of special treatment in the classroom. The teacher monitors the assignments of slow learners and the existence of mathematics learning videos sent by the teacher via WhatsApp. The role of parents is to be educators for students, parents are protectors of children, parents are priority students, and parents know the condition of students at home. The principal's role is to guide the teacher in the learning process, and there is an evaluation for the teacher. This study concluded that teachers, parents, and principals are very influential in overcoming the learning difficulties of slow learners.